Pemodelan Magicc-Scengen sebagai Acuan Strategis Mitigasi dan Adaptasi Perubahan Iklim Sektor Perikanan dan Kelautan - Syafrudin Raharjo; Suhaemi Suhaemi; Marhan Marhan (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
The rise of global surface temperature is predicted to increase the rainfall and runoff. Long-term changes in rainfall will affect the water resource, thus also influencing the fisheries and maritime sector. Understanding the global climate change and their effects, especially in Indonesia as one of the environmental condition parameters, is a part of the strategy for mitigation and adaptation towards climate change, and it is important to do early to support the sustainable development of Indonesia. Magicc-Scengen v5.3 is one of the widely-used climate models. Magicc is used in the projection of sea level and temperature, while Scengen is used to produce the regional climate change scenario with the resolution of 2.5°×2.5° latitude and longitude. This study aims to determine the climate change level especially the air temperature and rainfall in Indonesia using Magicc-Scengen model (global circulation model UKHADCM3 and UKHADGEM) using A1-BAIM and B2-MES scenarios. According to the Magicc-Scengen simulation model, in the year 2100, the global temperature will change from 2.5°C (B2-MES) towards 3°C (A1-BAIM). In Indonesia, the maximum change of temperature will occur on the A1-BAIM scenario, which is 2.12°C, distributed across Sumatra and Kalimantan. Moreover, on B2-MES scenario, the maximum temperature change is 1.88°C. The simulation results also show a rainfall escalation, from 25.4 towards 26.2%, in March-April-May (MAM) period. The A1-BAIM scenario determines that the highest rainfall will occur in MAM (for the year of 2050 and 2100), while B2-MES scenario determines that the rainfall pattern varies widely, in which the highest of it in 2050 will occur on December-January-February (DJF). However, for the year 2100, the highest rainfall will occur on MAM.